+0  
 
0
93
1
avatar

No idea how to solve this problem. 

Guest Sep 16, 2017
Sort: 

1+0 Answers

 #1
avatar+78575 
+1

We're not solving anything ....we just want to factor this as the difference of cubes

 

So we have

 

y^3 / 27    - x^9 / 216

 

Difference  of cubes  formula     

 

a^3 - b^3   =  (a - b)  (a^2  + ab  + b^2)

 

let a  = y / 3      b  = x^3 / 6       a^2  = y^2 / 9      ab  =  [y x^3 ] / 18      and    b^2 =  x^6 / 36

 

So we have 

 

( y / 3 - x^3 / 6) (  y^2 / 9  +   [y x^3 ] / 18  + x^6/ 36  )

 

 

cool cool cool

CPhill  Sep 16, 2017

3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details